2011
DOI: 10.1149/1.3505296
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Reaction Kinetics of the CO∕CO[sub 2]∕Ni∕YSZ Electrode

Abstract: Results of combined experimental and theoretical investigations of elementary chemical reaction processes of CO-CO 2 gas mixtures at nickel/yttria-stabilized zirconia ͑Ni/YSZ͒ solid oxide fuel cell ͑SOFC͒ model anode systems are presented. Temperature-programmed desorption and reaction measurements were performed in order to determine adsorption/desorption kinetic data as well as thermodynamic parameters for the CO/CO 2 /Ni and CO/CO 2 /yttria-stabilized zirconia ͑YSZ͒ heterogeneous reaction systems. From thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 30 publications
6
85
1
Order By: Relevance
“…Note that this electrochemical 13 approach also includes the gas-phase partial pressures, which are frequently neglected within the open literature and also in our previous models [3,37,44]. Here K eq the temperature dependent equilibrium constant for eqns (2) and (3), respectively and AV e is the electrochemically active surface area-to-volume ratio. For AV e an average value of 9·10 6 m 2 /m 3 is applied in this work, which can be compared to 70·10 6 m 2 /m 3 , the measured specific surface area for Ni/YSZ material developed for SOFC anodes [46].…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that this electrochemical 13 approach also includes the gas-phase partial pressures, which are frequently neglected within the open literature and also in our previous models [3,37,44]. Here K eq the temperature dependent equilibrium constant for eqns (2) and (3), respectively and AV e is the electrochemically active surface area-to-volume ratio. For AV e an average value of 9·10 6 m 2 /m 3 is applied in this work, which can be compared to 70·10 6 m 2 /m 3 , the measured specific surface area for Ni/YSZ material developed for SOFC anodes [46].…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
“…There are a variety of designs developed for FCs, but they all operate with the similar basics and principles [1]. FCs are promising candidates for providing electrical power for future energy systems due to the high efficiency and low emissions of NO x compared to conventional power generation systems [2]. The solid oxide fuel cell (SOFC) operates at temperatures between 600-1000°C [3].…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since experimental studies on SO-DCFC are rather complex, expensive, and time-consuming, comprehensive mathematical models are essential for the technology development. A validated mechanistic model would offer means to gain insight into the complex physical phenomena governing fthe uel cell performance that is not readily accessible experimentally, and it can also be useful tool for cell design and operating condition optimization.Modeling and experimental studies of SO-DCFCs have been reported recently by several researchers [6][7][8][9]. Numerous SOFC models considering the intricate interdependency among ionic and electronic conduction, gas transport phenomena, and electrochemical processes have been reported in the literatures for pure hydrogen, syngas or methane [10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…The standard approach to building models in such a case is to postulate reaction models and to compare them based on their ability to reproduce indirect system-level experimental data. Data-driven model comparison thus involves defining a metric of fit, e.g., the sum of squared residuals, and selecting a model that minimizes this metric, e.g., least-squares or regularized least-squares fitting (Hanna et al, 2014;Vogler et al, 2009;Yurkiv et al, 2011). The principal limitation of the least-squares fitting approach is that it only identifies a single "best" model and yields point estimates of the underlying parameter values, without providing a meaningful description of the uncertainty among competing models and in their parameters.…”
Section: Introductionmentioning
confidence: 99%